Origin of the Larger Values of Total Cross Section for Helium Scattering from Isolated Atomic Steps - Sultana, K.S.; Allison, W.; Hafiz, M.Z. (Dhaka University Journal of Science, 2012)
The effect of surface relaxation and the electronic re-arrangement in the vicinity of a step on the total step cross section for helium scattering is investigated. A realistic helium interaction potential at a Cu(001) step is modeled by summing non-spherical pair potentials which allows for the possibility of varying the smoothing across the surface due to the itinerant aspects of the surface electronic structure. Numerical calculations reveal a significant increase in the magnitude of the total step cross section with large charge re-arrangement in the vicinity of the step. Also, the relaxation of surface layers has no effect whatsoever. The present study clearly shows that the origin of the experimentally observed large step cross section is the hard wall scattering from charge re-arrangement in the proximity of the step. Further, the charge re-arrangements probed by thermal helium atoms must be greater than predicted by pairwise models. DOI: http://dx.doi.org/10.3329/dujs.v60i2.11532 Dhaka Univ. J. Sci. 60(2): 271-275, 2012 (July)